Influence of innovations on social-economic development: Views of academic economists - Tania Abdulrahman, Natalia Prodanova, Nataliya Plaskova, Alexander Samusenko,; Polyanskaya, Tatiana; Cernostana, Zanna (Opción, 2019)
The article presents an analytical review of economists’ materials, in which the role of innovation in the economy is considered in close relationship with the dynamics of socio-economic development. According to results of the review, the author concludes that the discussions of the global academic economists, including materials of Russian economists, formed the basis of the formation of both the whole science of the innovation theory, and certain areas in scientific fields: innovation management and economic analysis of innovative activity.